Empirical study on leading determinants of dividend policy by CIMB group 1993-2012 / Ahmad Jazmie Zuhrie Mohamad Kamar - Mohamad Kamar, Ahmad Jazmie Zuhrie (2013)
According to Chay and Suh (2005), different country will have their owned culture, rules and regulations restricted on the dividend policy and different country based corporate also practicing different policy. The policy between companies is depending on the company management decision and also others several factors. Baker, Farrelly, and Edelman (1985) support the Lintner findings, and they conclude that the major determinants of dividend payments are future earnings and past dividends. The objective of this research is to identify the determinants that influencing the dividend policy decision by the management of CIMB group. As per finding, researcher also supports the Lintner theory. Researcher found that earning and past dividend plays an important roles for CIMB group decide their dividend per share. All independent variable used in this model are acceptable to include in this study